The milkweed lands : an epic story of one plant, its nature and ecology - Lee-Mäder, Eric, 1972- (Storey Publishing, 2023)
"Ecologist Eric Lee-Mäder and noted botanical artist Beverly Duncan have teamed up to create this unique exploration of the complex ecosystem that is supported by the remarkable milkweed plant"--